Fire-human-climate interactions in the Bolivian Amazon rainforest ecotone from the Last Glacial Maximum to late Holocene - Maezumi, S. Yoshi; Power, Mitchell J.; Smith, Richard J.; McLauchlan, Kendra K.; Brunelle, Andrea R.; Carleton, Christopher; Kay, Andrea U.; Roberts, Patrick; Mayle, Francis E. (Frontiers in Environmental Archaeology, 2023)
The Amazon Rainforest Ecotone (the ARF-Ecotone) of the southwestern Amazon Basin is a transitional landscape from tropical evergreen rainforests and seasonally flooded savannahs to savannah woodlands and semi-deciduous dry forests. While fire activity plays an integral role in ARF-Ecotones, recent interactions between human activity and increased temperatures and prolonged droughts driven by anthropogenic climate change threaten to accelerate habitat transformation through positive feedbacks, increasing future fire susceptibility, fuel loads, and fire intensity. The long-term factors driving fire in the ARF-Ecotone remain poorly understood because of the challenge of disentangling the effects of prolonged climatic variability since the Last Glacial Maximum (LGM; ~24,000 to 11,000 cal BP) and over 10,500 years of human occupation in the region. To investigate this issue, we implement an interdisciplinary framework incorporating multiple lake sediment cores, with varying basin characteristics with existing regional palaeoclimatological and archaeological data. These data indicate expansive C4 grasslands coupled with low fire activity during the LGM, higher sensitivity of small basins to detecting local-scale fire activity, and increased spatial diversity of fire during the Holocene after ~10,500 cal yr BP to the limit of our records ~4000 cal yr BP, despite a similar regional climate, may be attributed to increased human-driven fire. These data add to an increasing body of evidence that Indigenous peoples have a long, multi-millennial history of managing ecosystems that may shape modern biodiversity patterns in the ARF-Ecotone.